Liquidity effects and FFA returns in the international shipping derivatives market - Alizadeh, Amir H.; Kappou, Konstantina; Tsouknidis, Dimitris; Visvikis, Ilias D. (My University, 2015)
. The study examines the impact of liquidity risk on freight derivatives returns. The Amihud liquidity ratio and bid-ask spreads are utilized to assess the existence of liquidity risk in the freight derivatives market. Other macroeconomic variables are used to control for market risk. Results indicate that liquidity risk is priced and both liquidity measures have a significant role in determining freight derivatives returns. Consistent with expectations, both liquidity measures are found to have positive and significant effects on the returns of freight derivatives. The results have important implications for modeling freight derivatives, and consequently, for trading and risk management purposes.
Keywords: Bid-ask spreads; Forward freight agreements; Liquidity risk; Panel data; Shipping